Autoimmune (IgG4-related) Pancreatitis and Cholangitis - Levy, Michael J.; Chari, Suresh T.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Autoimmune (IgG4-related) Pancreatitis and Cholangitis reviews the breadth of clinical, imaging, histological, laboratory, and imaging features associated with IgG4-associated systemic disease, especially AIP and IAC. Written by experts in their fields, each chapter includes an overview of existing data as well as the most up-to-date scientific information and emerging data. The book also addresses areas of uncertainty and controversy, briefly highlighting clinical and research needs relative to the respective topic. Comprehensive and easy to use, Autoimmune (IgG4-related) Pancreatitis and Cholangitis is a valuable resource for physicians who deal with or are interested in these complex disease processes, including gastroenterologists, hepatologists, and surgeons.
Background and Perspective -- Immune Pathogenesis -- Overview of Types 1 and 2 -- Histologic Features -- CT and MRI Features -- EUS Features -- ERCP Features -- Clinical Features -- Approach to Diagnosis -- Surgical Implications -- Approach to Therapy -- Secondary Sclerosing Cholangitis -- Histologic Features -- CT and MRI Features -- ERCP and EUS/IDUS Features -- Clinical Spectrum and Management -- Overview -- Tubulointerstitial Nephritis and other Renal Involvement by IgG4-Related Disease -- IgG4-related Lung Disease -- Italian Experience -- British Experience -- Japanese Experience -- Korean Experience -- Summary and Look to the Future.
Keywords: Medicine; Gastroenterology; Clinical medicine; Emergency medicine; Rheumatology; Medicine & Public Health; Gastroenterology; Hepatology; Rheumatology; Primary Care Medicine